2022
DOI: 10.3390/nu14183831
|View full text |Cite
|
Sign up to set email alerts
|

Tube Feeding in Neurologically Disabled Children: Hot Topics and New Directions

Abstract: Tube feeding is a therapeutic intervention that is aimed at providing nutritional support and is important in the nutritional and gastrointestinal management of children with neurological disability (ND) worldwide. Since the publication of the first European Society of Gastroenterology, Hepatology, and Nutrition (ESPGHAN) consensus paper in 2017, some aspects of tube-feeding modalities have attracted the interest of the scientific community more than others, including the type of enteral formulas, enteral acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
4
0
3
Order By: Relevance
“…A significant number of children with NIs encounter difficulties with swallowing and gastrointestinal symptoms. As a result, these children frequently necessitate tube feeding to enhance their nutritional status and promote healthy growth, ensure sufficient fluid intake, and enhance adherence to medication regimens (21,22). Liu et al (23) conducted a study that revealed a positive correlation between NI and the occurrence of both early and late complications associated with gastrostomy.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of children with NIs encounter difficulties with swallowing and gastrointestinal symptoms. As a result, these children frequently necessitate tube feeding to enhance their nutritional status and promote healthy growth, ensure sufficient fluid intake, and enhance adherence to medication regimens (21,22). Liu et al (23) conducted a study that revealed a positive correlation between NI and the occurrence of both early and late complications associated with gastrostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the type of enteral formula in children with ND did not predict the normalization of nutritional status. The choice of enteral formula comes from different factors, including the patient’s age, nutritional requirements, type of enteral access, and child’s tolerance to feeds [ 7 , 20 , 21 ]. A standard (1.0 kcal/mL) polymeric age-appropriate formula including fiber is recommended as the initial enteral feed after 1 year of age [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enteral nutrition can be performed as intermittent boluses or continuously (165). Children with increased caloric requirements or poor volume tolerance may benefit from a combination of continuous nocturnal enteral nutrition combined with multiple boluses during the day (166).…”
Section: Enteral Feeding By Tubementioning
confidence: 99%
“…For neurologically impaired children with PEG, some natural food options that can be incorporated into their diet include: fruits and vegetables that are rich in vitamins, minerals, and antioxidants and can be easily blended into their feeding regimen; whole grains such as rice, oats, and quinoa, which provide carbohydrates, fiber, and essential nutrients; lean protein sources such as chicken, fish, and eggs that provide essential amino acids; and healthy fats such as avocado, nuts, and seeds that are rich in omega-3 fatty acids. Dairy products such as milk, yogurt, and cheeses are also good sources of calcium for bone health (166,173,174). Formulas containing natural foods have been shown to enhance tolerance and feeding outcomes, improve family participation, and increase compliance during mealtimes (175).…”
Section: Enteral Feeding By Tubementioning
confidence: 99%